GREEN MARKETING ANALYSIS IN IMPROVING CONSUMER LOYALTY - Muh. Husriadi; Munawir Makmur; Muhammad Aswin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The coffee shop industry in Indonesia is facing fierce competition​ at a time increasing awareness consumer on environmental issues, so that the implementation of green marketing is an important strategy to increase loyalty consumers. This study aims to analyze green marketing implementation and its influence on loyalty consumers in coffee shop business actors. Method qualitative with a case study approach is used through interview in-depth, observation, and document study. The results of the study show that the implementation of green products, green processes, and green places is significant increase perception positive and loyalty consumers. Effective green marketing education and promotion also play an important role in shaping awareness consumers . However, business actors face constraint in the form of high costs, limitations knowledge, and support suppliers that are not optimal. The implications of this research emphasize importance training, collaboration with suppliers, and utilization of digital technology to strengthen green marketing strategies and sustainability of coffee shop businesses. This study contributes theoretical and practical in the development of sustainable marketing in the sector service.